Activities of Various 4-Aminoquinolines Against Infections with Chloroquine-Resistant Strains of Plasmodium falciparum - Schmidt, L. H. (1977)
The studies reported here stemmed from a personal report by Geiman on the capacity of the 4-aminoquinoline amodiaquin to inhibit in vitro maturation of ring stages of the chloroquine-resistant Monterey strain of Plasmodium falciparum. This observation, confirmed in owl monkeys infected with this strain, led to a comparison of the activities of chloroquine, amodiaquin, amopyroquin, and dichlorquinazine (12,278 RP) against infections with various chloroquine-susceptible and chloroquine-resistant strains. The results showed that: (i) these 4-aminoquinolines were essentially equally active against infections with chloroquine-susceptible strains and (ii) the activities of amodiaquin, amopyroquin, and dichlorquinazine were reduced significantly in the face of chloroquine resistance, but (iii) well-tolerated doses of these compounds would cure infections with strains that fully resisted treatment with maximally tolerated doses of chloroquine. Two other 4-aminoquinolines, SN-8137 and SN-9584, which also exhibited activity against chloroquine-resistant parasites in vitro, displayed curative activity in monkeys infected with a chloroquine-resistant strain. These observations show that there is cross-resistance among the 4-aminoquinolines, confirming earlier findings, but indicate that the dimensions of this phenomenon are sufficiently limited so that some derivatives are therapeutically effective against infections refractory to maximally tolerated doses of chloroquine.